Tutor, teacher, educator in a culturally diverse space of modern education - Młynarczuk-Sokołowska, Anna (Kultura-Społeczeństwo-Edukacja, 2019)
The main purpose of this paper is the presentation of selected issues regarding the preparation of tutors, teachers, educators and students who are going to work in the education field and in culturally diverse educational spaces. The first part of the article presents this issue, based on the analysis of the literature. The second part includes examples of initiatives which enable the development of intercultural competence pursued by the author of this paper.